2020
DOI: 10.1128/msystems.00843-19
|View full text |Cite
|
Sign up to set email alerts
|

Proton Nuclear Magnetic Resonance Metabolomics Corroborates Serine Hydroxymethyltransferase as the Primary Target of 2-Aminoacrylate in a ridA Mutant of Salmonella enterica

Abstract: The reactive intermediate deaminase RidA (EC 3.5.99.10) is conserved across all domains of life and deaminates reactive enamine species. When Salmonella enterica ridA mutants are grown in minimal medium, 2-aminoacrylate (2AA) accumulates, damages several pyridoxal 5′-phosphate (PLP)-dependent enzymes, and elicits an observable growth defect. Genetic studies suggested that damage to serine hydroxymethyltransferase (GlyA), and the resultant depletion of 5,10-methelenetetrahydrofolate (5,10-mTHF), was responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…The relative number of energy biosynthesis and degradation pathways affected by carvacrol in this study suggests that, perhaps, carvacrol acted largely on the energy biosynthesis pathways, thereby eliciting the global changes in the metabolome of X. perforans. A recent study has shown that global metabolic changes may be a consequence of a cascade of responses initiated by a unique metabolite [157,158]. It is, therefore, likely that the global changes identified in X. perforans were due to the activities of carvacrol on specific pathways.…”
Section: Pathway Analyses Suggest That Carvacrol Elicits Global Metab...mentioning
confidence: 99%
“…The relative number of energy biosynthesis and degradation pathways affected by carvacrol in this study suggests that, perhaps, carvacrol acted largely on the energy biosynthesis pathways, thereby eliciting the global changes in the metabolome of X. perforans. A recent study has shown that global metabolic changes may be a consequence of a cascade of responses initiated by a unique metabolite [157,158]. It is, therefore, likely that the global changes identified in X. perforans were due to the activities of carvacrol on specific pathways.…”
Section: Pathway Analyses Suggest That Carvacrol Elicits Global Metab...mentioning
confidence: 99%
“…NMR measurements of chemically defined spent minimal media, spent minimal media supplemented with isoleucine, and the resulting cell pellets demonstrated that key metabolite changes between ridA and wild-type strains were due to the IlvA-dependent generation of 2AA. Further media supplementations circumvented the downstream pathway damage to GlyA, largely restoring those same endogenous and exogenous metabolites to wild-type levels . This classical genetic perturbation and metabolome rescue approach, and the agreement between media analysis and bacterial endometabolome, disentangled the complex metabolic relationships between enzymes and further expanded the interacting edges of the known ridA biochemical model to previously unexplored pathways. , …”
Section: Model Microorganisms and Metabolismmentioning
confidence: 99%
“…The role that metabolomics play together with the other 'omics' technologies in the understanding of complex biological systems is broadly accepted. Many Life Science projects have implemented untargeted metabolomics within their pipeline to help them characterize phenotypes for different applications [5,6,7,8,9,10,11,12]. However, one of the major bottlenecks to be overcome in this approach is compound identification, since important features with no identification lead to no meaningful understanding of a biological system [13,14].…”
Section: Metabolomics and Spectroscopymentioning
confidence: 99%